Lockerbie : the story and the lessons - Wallis, Rodney, 1933- (Praeger, 2001)
The story of the Lockerbie tragedy from the build-up of the terrorist threat in the summer of 1988 to the indictment of Libyan agents for their part in the bombing. It examines the facts surrounding the sabotage of the flight and the weaknesses in Pan Am's communication and management policies.